2017
DOI: 10.1089/jmf.2016.0080
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hypotensive and Antihypertensive Effects of Velvet Bean (Mucuna pruriensL.) Hydrolysates

Abstract: Hypertension could cause significant worldwide health problems that affect 15-20% of all adults; according to National Health and Nutrition Examination Survey, about 29% of the adult population in the United States are hypertensive. Recent research has shown that peptides derived from the hydrolysis of food proteins can decrease blood pressure. This study was carried out to evaluate the hypotensive and antihypertensive potential of Mucuna pruriens protein hydrolysates in in vitro and in vivo models. M. prurien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…Thus, during the initial stage of enzymatic hydrolysis, the hydrolysis degree increased, and the content of antioxidant peptides and the DPPH radical scavenging activity also increased. At the later stage of enzymatic hydrolysis, some long-chain antioxidant peptides can be hydrolyzed, which might have caused the decrease in DPPH radical scavenging activity (Chel-Guerrero et al 2016). These findings indicated that time is also an important factor in the hydrolyzation of duck meat.…”
Section: Resultsmentioning
confidence: 94%
“…Thus, during the initial stage of enzymatic hydrolysis, the hydrolysis degree increased, and the content of antioxidant peptides and the DPPH radical scavenging activity also increased. At the later stage of enzymatic hydrolysis, some long-chain antioxidant peptides can be hydrolyzed, which might have caused the decrease in DPPH radical scavenging activity (Chel-Guerrero et al 2016). These findings indicated that time is also an important factor in the hydrolyzation of duck meat.…”
Section: Resultsmentioning
confidence: 94%
“…The antihypertensive effects of the hydrolysates were sustained at all time points throughout the experiments, in line with the effect induced by the administration of captopril ( p < 0.05 for all treatments, except water, compared to basal values (time zero)) ( Figure 3 ). Similar antihypertensive effects have been reported using food-protein hydrolysates derived from sources others than chickpeas, such as amaranth (about 59 mmHg of systolic blood pressure reduction after 6 h of the hydrolysate administration; [ 4 ], flaxseed (−29 mmHg at 4 h [ 33 ]), lima bean (51% systolic blood pressure reduction after two weeks of daily supplementation of the hydrolysates; [ 34 ]), velvet bean (8.84–27.29% of systolic blood pressure reduction after 0–140 min of the hydrolysates administration; [ 35 ]), rice bran (−34 mmHg systolic blood pressure reduction after 6 h of the hydrolysate administration; [ 36 ]), and pigeon pea (−33 mmHg after 4 h of the hydrolysate administration [ 37 ]). Overall, the results show that both the unextruded and the extruded chickpea protein hydrolysates not only have the potential to inhibit ACE-I in vitro, but also have the potential to lower the systolic blood pressure in spontaneously hypertensive rats.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Chel‐Guerrero et al assessed M. pruriens ‐derived hydrolysates produced separately with the Alcalase® and Flavourzyme® enzymes at different hydrolysis times. At a 5 mg kg −1 concentration, the Alcalase® hydrolysates produced at 90 min reduced BP by 25.53 ± 5.46%, although this did not differ ( P > 0.05) from the Flavourzyme® hydrolysates produced at 90 min (29.37 ± 13.03%) or the Captopril® control (28.56 ± 5.23%).…”
Section: Resultsmentioning
confidence: 99%
“…5 Different peptides derived from several legumes (e.g. velvet bean Mucuna pruriens, 7 cowpea Vigna unguiculata and Jamapa bean Phaseolus vulgaris), exhibit antihypertensive activity. 8,9 Lima bean Phaseolus lunatus has a high nutrient content and is a potential source of bioactive 782 www.soci.org NA Ciau-Solís, JJ Acevedo-Fernández, D Betancur-Ancona peptides with antihypertensive, antithrombotic, anticancer and antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%